Moderating role of human resource competence: Information technology and internal control's impact on regional financial report quality - Prasetio, Allung; Majid, Jamaluddin; Juardi, Muhammad Sapril Sardi (Advances in Applied Accounting Research, 2023)
Purpose: This study aims to investigate the impact of information technology and internal control on the quality of financial reports, with human resource (HR) competency serving as a moderating variable. The hypothesis tested is whether HR competency can strengthen or weaken the relationship between the independent variables and the quality of financial reports. Research Design and Methodology: This quantitative, causality-focused research involved 52 respondents from the SKPD (Regional Work Units) of the Luwu Utara Regency Government, selected through purposive sampling based on a minimum of one year of service. Primary data were collected via questionnaires and analyzed using SPSS 25. Standard assumption tests were conducted, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Hypotheses were tested using multiple linear regression and moderation regression analysis with interaction terms. Findings and Discussion: The results reveal that internal control has a positive and significant effect on the quality of financial reports, whereas information technology does not show a significant impact. However, HR competency successfully moderates the relationship between information technology and financial report quality but not between internal control and financial report quality. Implications: The findings suggest that strengthening HR competency is essential to maximizing the benefits of information technology in financial reporting. Further studies are recommended to investigate these dynamics across various regions and sectors, facilitating broader policy applications.